The Influence of Product Innovation, HR Competence, and Marketing Performance on The Financial Performance of MSMEs in The Agricultural - Kuswardani, DC.; Santoso, Aprih; Maulana, Dede Yusuf; Alfiana; Gusmao, Cristino (Jurnal Manajemen dan Agribisnis, 2024)
Background: Many MSMEs are switching to online businesses and utilizing digital technology to maintain their businesses.Purpose: This study aims to determine and examine the effect of product innovation, HR competency, and marketing performance on the financial performance of MSMEs in the Agricultural Sector in Semarang City after the Covid-19 pandemic with digitalization as a mediating variable.Design/methodology/approach: This study uses quantitative methodology and a causal associative approach. Data was collected through an online questionnaire distributed to MSME owners in the Agricultural Sector via WhatsApp, with questions filtered based on respondent characteristics. The sampling technique used was random sampling. The number of samples in this study was 150 business owners. Data analysis used partial least squares-structural equality modeling (PLS-SEM).Findings/Results: The results of this study indicate that product innovation, marketing performance, and digitalization have a significant effect on financial performance. Meanwhile, HR competency has had no significant effect on the financial performance of MSMEs in the Agricultural Sector in Semarang City after the COVID-19 pandemic. Digitalization has been proven to mediate the influence of product innovation, HR competency, and marketing performance on the financial performance of MSMEs in the Agricultural Sector in Semarang City.Conclusion: Product innovation, marketing performance, and digitalization have a significant effect on financial performance. Meanwhile, HR competency has not had a significant effect on the financial performance of MSMEs in the agricultural sector in Semarang City since the COVID-19 pandemic. Digitalization is proven to mediate the influence of product innovation, HR competency, and marketing performance on the financial performance of MSMEs in the Agricultural Sector in Semarang City.Originality/value (State of the art): State of the art in the era of digital transformation. Given that digitalization is increasingly becoming an important part of the global economy, this study is relevant to the current trend of digital technology adoption by MSMEs. This study can broaden the understanding of how small and medium-scale MSMEs can utilize digitalization to improve their competitiveness and financial performance, which is a growing research area globally. Keywords: digital transformation, HR competency, marketing performance, MSME finance, product innovation